The intervention of Brain Gym in the mathematical abilities of high-school students: A pilot study - Ramos-Galarza, Carlos; Aymacaña-Villacreses, Cristina; Cruz-Cárdenas, Jorge (Frontiers in Psychology, 2023)
The learning process of Mathematics is a challenge in Latin America; therefore, it is of vital importance to conduct actions that improve the performance in this science. This article is reporting on quasi-experimental research, where, through the use of Brain Gym, the objective is to improve: the definition of rational numbers, problem-solving ability, mathematical order relationships, and equivalent fractions. We worked with 67 students between 12 and 14 years old, organized into an experimental group (n = 35) and a control group (no participation group) (n = 32). We made pre and post-test measurements and found that the control group students improved in their problem-solving ability F (1, 65) = 8.76, p = .04, η2 = .12 and equivalent fractions F (1 , 65) = 4.54, p = .03, η2 = .06. In conclusion, the importance of applying innovative processes to improve the teaching and learning of Mathematics can be affirmed. It is important to note that both the control and experimental groups improved their learning, however, the experimental group did so to a greater extent than the students in the control group, who received a traditional educational process, and they did learn, but not at the level of the experimental group.